Participatory Financing Instruments Formula "Murabaha Model" - Mafhoum, Ahmed; Al Baraka, Abdul Basit (Journal of Neonatal Surgery, 2025)
Crowdfunding is based on principles that frame the parties to the contractual process, including prohibiting contracts based on exploiting people and eating their money unjustly, such as dealing with usury, fraud, and obscenity in achieving unlawful profits. After the legal provision for the establishment of participatory banks and their commencement of operation in the Kingdom of Morocco, people breathed a sigh of relief and were freed from the embarrassment caused by dealing with financial institutions that do not observe the provisions of Islamic Sharia. Participatory banks can deal with six financing formulas as stipulated by the law, among these formulas is the Murabaha formula, which has gained popularity and acceptance among people due to the ease of dealing with it and the clarity of the terms of its contracts on the one hand, and on the other hand, the preference of banking institutions to deal with it because of the profits it achieves without great cost and because it carries less risk than dealing with other formulas. This research aims to demonstrate the achievement of contractual justice between the banking institution and its customers when dealing with the Murabaha formula, where the most important results were reached: The purpose of the concept of justice is to give everyone his due right without injustice. Financial transactions are not fully enforceable and do not have an effect unless they achieve the principle of justice between the parties. The contract between the parties satisfies the societal contract based on security and stability, and whenever justice differs between the parties, the balance in society is disturbed. Achieve full acceptance and approval in the Murabaha contract between the bank and the merchant, and the bank and the customer (the purchase orderer), without any defect of will. This satisfaction may be expressed by acceptance and approval or by signing the contract concluded between the merchant and the bank or between the bank and the purchase orderer.